Semantic Production of the Sign in the Dramatic Act of TV Series: محمد سمير محمد (Al-Academy, 2019)
The researcher, in this academic research, seeks to highlight the role of the semantic production in the dramatic act and to know the extent of its work and importance, because drama is an act and the dramatic work is a group of acts. The dramatic meaning and act are two inseparable concepts that cannot be divided, because each dramatic act is a container of meanings through connotations, signs and symbols. The production of the connotations in the dramatic act is considered one of the important issues in the content language of communication between the sender and recipient in order to get to the intended meaning. These sign connotations engage the spectator in the codifying activity and get him immersed in the events. The research presents ways and methods through which the semantic production of the sign in the dramatic act is done through the results reached at